2013
DOI: 10.1177/0047287512475217
|View full text |Cite
|
Sign up to set email alerts
|

“Do We Believe in TripAdvisor?” Examining Credibility Perceptions and Online Travelers’ Attitude toward Using User-Generated Content

Abstract: Recent press reports and complaints by hoteliers have called into question the credibility of travel-related user-generated content (UGC). Yet our understanding of the role of credibility perceptions in the context of UGC is limited, notwithstanding the rising interest in social media. Using an online survey of 661 travel consumers, this study applies the component-based structural equation modeling technique of partial least squares to examine online travelers' perceptions of the credibility of UGC sources an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
375
3
35

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(466 citation statements)
references
References 65 publications
(98 reference statements)
16
375
3
35
Order By: Relevance
“…The selection of information sources and the degree of accumulated satisfaction are also dependent on several factors that induce barriers (or facilitating conditions) to the information search process. Trust perceptions on the information source and personal traits, in the form of individuals' age, gender and information literacy skills, have been reported to influence both the selection of information sources and the resulting satisfaction beliefs from the consumed information [13,52,62]. M a n u s c r i p t 6 Our study proposes that travellers may achieve information satisfaction through combinations of groups of information needs, utilization of specific online information sources and interventions of specific information obstacles/facilitators.…”
Section: Research Propositionsmentioning
confidence: 85%
See 1 more Smart Citation
“…The selection of information sources and the degree of accumulated satisfaction are also dependent on several factors that induce barriers (or facilitating conditions) to the information search process. Trust perceptions on the information source and personal traits, in the form of individuals' age, gender and information literacy skills, have been reported to influence both the selection of information sources and the resulting satisfaction beliefs from the consumed information [13,52,62]. M a n u s c r i p t 6 Our study proposes that travellers may achieve information satisfaction through combinations of groups of information needs, utilization of specific online information sources and interventions of specific information obstacles/facilitators.…”
Section: Research Propositionsmentioning
confidence: 85%
“…For example, online social media have emerged as a primary information source that affects destination choice [9][10][11]. However, the abundance of information within social networks may lead to information A c c e p t e d M a n u s c r i p t 2 overload [12] and often incorporate misleading or unreliable information [13]. In effect, the online information-seeking process of travellers is rather complex; travellers are motivated to select and use multiple online information sources based on inherent travel-related information needs that relate to the vacation planning decision-making [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that most academic research on TripAdvisor is found in the tourism literature and focuses on hotel reviews. Previous studies tend to focus on practical issues such as how users decide how to trust reviews, the response of hotels to reviews, or the content of negative reviews and complaints (O 'Connor, 2008;Cunningham et al, 2010;Sparks and Browning, 2010;Stringam and Gerdes, 2010;Ayeh et al, 2013). In contrast, our substantive interest, discussed elsewhere, is in how TripAdvisor works to convey cultural meanings.…”
Section: Case Selectionmentioning
confidence: 98%
“…Moreover, other researchers established a positive relationship between source and message credibility and attitudes (e.g., Hovland, Janis, & Kelley, 1953); as well as credibility and attitude within a commercial context (e.g., Ayeh, Au, & Law, 2013;Lafferty, Goldsmith & Newell, 2002;Ohanian, 1991;Pornpitakpan, 2004). For instance, Ayeh et al's (2013) examination of user generated content found that the credibility dimensions of trust and perceived expertise significantly influence attitudes toward online content.…”
Section: Message Credibilitymentioning
confidence: 99%